Progress in Artificial Economics Computational and Agent-Based Models - Li Calzi, Marco.; Milone, Lucia.; Pellizzari, Paolo. (Lecture Notes in Economics and Mathematical Systems, 2010)
Artificial economics aims to provide a generative approach to understanding problems in economics and social sciences. It is based on the consistent use of agent-based models and computational techniques. It encompasses a rich variety of techniques that generalize numerical analysis, mathematical programming, and micro-simulations. The peer-reviewed contributions in this volume address applications of artificial economics to markets and trading, auctions, networks, management, industry sectors, macroeconomics, and demographics and culture.